Supramolecular chemistry of small molecular fundamentals to drug–receptor applications - Welideniya, Dhanushi Thathsara (Kansas State University, 2015)
A family of bis-pyridine based pharmaceutical active ingredients were synthesized and co-crystallized with four iodoperfluoroalkanes. Thirteen new crystal structures that are driven by I‧‧‧N(py) halogen bonds, are presented and compared with that of their hydrogen-bonded analogues. Halogen bonded co-crystals exhibit two different structural arrangements, as opposed to layered architectures observed in hydrogen bonded co-crystals. In order to explore the effect of aromatic stacking interactions on hydrogen and halogen bond driven co-crystallization process, we utilized a series of aromatic hydrogen and halogen bond donors in combination with bis-pyridine based pharmaceutical active ingredients. Aromatic stacking between the donor and the acceptor were limited, due to the lack of complementarity between the donor and the acceptor in terms of size, shape and geometry. In that case, homomeric interactions between the single components were translated into the structure of the binary co-crystals. According to our charge calculations, similarly activated hydrogen and iodine atoms possess similar electrostatics. Therefore, we wanted to investigate the interchangeability of hydrogen bonds and halogen bonds by utilizing 2-aminopyrimidine as the backbone for C(sp)-H and C(sp)-I functionalities which makes self-complementary ribbons via NH‧‧‧N synthons. Our results show that the ethynyl proton is capable of acting as a synthon mimic of ethynyl iodine by interchangeable C(sp)-H‧‧‧N hydrogen bonds and C(sp)-I‧‧‧N halogen bonds. We exploited the halogen bonding donor capability of iodo, bromo and chloro ethynyl functionalities towards a series of halide ions. Based on the grinding experiments these donors showed 90%, 70% and 50% success rates towards halides. Among the halides, chlorides exhibited the highest red shift compared to bromides and iodides. We synthesized a series of cavitands functionalized with hydrogen bond donor and acceptor groups and studied their binding preferences towards a series of active ingredients. We have shown that suitably functionalized cavitands can act as carriers of active ingredients and especially, selective binding of aspirin is demonstrated using a two-point binding mode.
Keywords: Halogen bonds; Synthon mimics; Anion recognition; CavitandsHydrogen bonds; Chemistry (0485)